Refresher in Basic Mathematics - Rowe R.N (Dp Publications Ltd, 1990)
This book is aimed at those students who have difficulty with basic mathematics as well as those who wish to refresh their understanding of the subject (perhaps due to a prolonged absence from study). Fractions, Decimals, Percentages, Elementary Algebra, Powers, Coordinates and Graphs, The Straight Line, Simple Linear Equations, Simultaneous Equations, Quadratic Equations, Achievement Test, Tutors Section, Appendices, A Note on Calculators, Rounding.